Application of Team Quiz Strategy to Improve Speaking Skills of Class VIII MTs. N 3 Gorontalo Regency - Rahayu Dunggio, Khairiyah; N. Hula, Ibnu Rawandhy; Hairuddin, Hairuddin (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
The purpose of this study is to determine the improvement of the maharah kalam ability of class VIII MTs Negeri 3 Kabupaten Gorontalo students by using a team quiz strategy. This research is a Class Action Research conducted at MTs Negeri 3 Gorontalo Regency. This research was carried out in 2 cycles. The data collection techniques used are observation, interviews, tests and documentation. The data analysis techniques used are descriptive and quantitative qualitative data analysis. The subjects of this study were students of class VIII C MTs Negeri 3 Gorontalo Regency, totaling 25 students. This research was conducted through 4 stages, namely the planning stage, implementation of actions, observation and reflection. The results of this study show that the application of the team quiz strategy can improve students' maharah kalam. This increase can be seen from the average value of the pre-test results, which is 33.2. After applying the team quiz strategy on the post test cycle 1 the average score result increased to 62.2, then in the post test cycle II the average score result increased to 79.8. With a successful pre-test result of 0%, post test cycle I 24% and post test cycle II 80%. Thus, it can be concluded that the team quiz strategy can improve the maharah kalam of class VIII MTs Negeri 3 students of Gorontalo Regency.